Inovasi Terkini dalam Penelusuran dan Pemulihan hunian negara - Eka Rosanti , Febrin (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2025)
The search for and recovery of country assets in the form of Country Residences by Higher Education institutions has become an interesting phenomenon in Indonesia and has become an open secret that has resulted in no profitable resolution for these institutions. In its development, State Houses are closely related to the increasing number of citizens who use State Houses for reasons other than their function, for example for business activities and carry over of rights. This article aims to answer the current strategy in tracing and recovering country assets in the form of Seat of government, answering questions about how to overcome non-transparency, legal problems and corruption related to state assets. This article uses a case approach and a literature study approach. The results of the research are recommendations for the latest inovasies such as routine audits, strengthening laws, strengthening databases, establishing a special task unit tasked with bringing order to the State House and eradicating corruption. The conclusion of this article is a strategy to grow the productiveness and cost efficiency of the use countryassets so that it ultimately benefits the people and economy of Indonesia.